Dear Mrs. Roosevelt : letters from children of the Great Depression - Cohen, Robert (Robby); Roosevelt, Eleanor, 1884-1962 (University of North Carolina Press, 2002)
Activism made Mrs. Roosevelt a beloved figure among poor teens and children, who between the Depression of 1933 wrote her thousands of letters describing their problems and requesting her help. Here are 200 of these extraordinary documents to open a window into the lives of the Depression's youngest victims. Illustrations.